Use of SQP optimization algorithm to size a multiphysical system: Application to an aircraft electrical power channel. Issue 2 (5th March 2018) - Tran, Le Nhat Hoang; Gerbaud, Laurent; Retière, Nicolas; Nguyen Huu, Hieu
Abstract : Purpose: Static converters generate current harmonics in power grids. For numerous studies, analytical frequency modeling is preferred to carry out their harmonic modeling in the context of sizing by optimization. However, a design by optimization has to consider other constraints, e.g. modeling constraints and operating constraints. In this way, this paper aims to focus on applying an analytical frequency modeling on the sizing by optimization of an aircraft electrical power channel. Design/methodology/approach: The paper aims to size a multiphysical system by optimization. In this way, the sizing of an aircraft electrical power channel by optimization has been carried out. The models of all the channel components are analytical. Specifically, the frequency model of the power electronics is based onTran et al. (2016 ) and is made of equalities and inequalities. Due to this modeling choice, the optimization satisfies hundreds of constraints, such as modeling constraints and static converter operating constraints. Furthermore, transient constraints are only verified after optimization. Findings: The difficulty is the modeling of the system by taking into account nonlinear implicit equations having several solutions. A solution is the addition of inequality constraints to the model to guide the implicit solving. Furthermore, this greatly helps the optimization algorithm to find the good operating mode of the static converter, at steady state. This aspect is indispensable to validate the sizing model. Research limitations/implications: The number of the configurations per operating period of the static converters is defined a priori and limited. Originality/value: The analytical model for the sizing is formulated as a constrained optimization problem. Its solving and the sizing by optimization are carried out by the same optimization algorithm.